2006
DOI: 10.1124/jpet.106.101444
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol Protects Diabetic Rats from Vascular Inflammation via Nuclear Factor-κB-Dependent Down-Regulation of Vascular Cell Adhesion Molecule-1 Expression

Abstract: Vascular cell adhesion molecule (VCAM)-1 plays a critical role in the initiation and development of vascular inflammation and selective inhibition of adhesion molecules expressed by endothelial cells may present a new therapeutic strategy for the treatment of vascular complications associated with diabetes mellitus. Increasing evidence indicates that cilostazol, a cAMP phosphodiesterase inhibitor, reduces VCAM-1 expression on endothelial cells. In this study, we have tested the effect of cilostazol on the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
5
23
0
Order By: Relevance
“…Treatment with cilostazol significantly reduced the inflam-matory marker highly-sensitive C-reactive protein (p = 0.03), endothelial markers E-selectin (p < 0.001) and solu-ble vascular cell adhesion molecule-1 (p < 0.001). Results of the study suggest that renal deterioration resulting from an upregulated immune response mediated by NF-ĸB-induced inflammatory and endothelial markers may be suppressed with cilostazol by inhibiting NF-ĸB [15][16][17]. Additionally, as supported by another study, cilostazol may ameliorate peripheral arterial occlusion disease, a macro-vascular complication of diabetes mellitus, in patients with type 2 diabetes mellitus by attenuating pro-inflammatory markers [18].…”
Section: Diabetic Nephropathysupporting
confidence: 51%
“…Treatment with cilostazol significantly reduced the inflam-matory marker highly-sensitive C-reactive protein (p = 0.03), endothelial markers E-selectin (p < 0.001) and solu-ble vascular cell adhesion molecule-1 (p < 0.001). Results of the study suggest that renal deterioration resulting from an upregulated immune response mediated by NF-ĸB-induced inflammatory and endothelial markers may be suppressed with cilostazol by inhibiting NF-ĸB [15][16][17]. Additionally, as supported by another study, cilostazol may ameliorate peripheral arterial occlusion disease, a macro-vascular complication of diabetes mellitus, in patients with type 2 diabetes mellitus by attenuating pro-inflammatory markers [18].…”
Section: Diabetic Nephropathysupporting
confidence: 51%
“…7 Cilostazol has also been shown to protect diabetic rats from vascular inflammation. 8 Research has shown that cilostazol inhibits protein kinase C (PKC) activity at the phosphoinositide-3 (PI-3) kinase level, which suppresses nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activation in the presence of phorbol 12-myristate 13-acetate (PMA) or tumour necrosis factor (TNF)-α. 9 By inhibiting the PI-3 kinasedependent pathway, cilostazol prevents the oxidative stress caused by the NADPHinduced release of reactive oxygen species, which may protect against the development of diabetic nephropathy.…”
Section: Renal Protective Effects Of Cilostazolmentioning
confidence: 99%
“…12 Expression of a large number of inflammation proteins is increased via NF-KB. 20 In contrast to many studies done about the role of NF-KB in different systems like the immune system, there are a few studies on the role of NF-KB in the nervous system. NF-KB is expressed in neurons and glial cells in central and peripheral nervous systems.…”
Section: Discussionmentioning
confidence: 98%